Interdependence in supply chains and projects in construction - Bankvall, Lars; Bygballe, Lena E.; Dubois, Anna; Jahre, Marianne (Supply chain management, 2010)
Purpose - The aim of this paper is to inquire into the management of construction supply chains by directing attention toward the different types of interdependencies that exist in such chains and in construction projects.Design methodology approach - The paper is developed as part of two ongoing research projects on supply chain management (SCM) in construction. A case study approach is used for illustrating the production and subsequent delivery and installation of plasterboards to a specific construction project. This description reveals extensive coordination among a number of companies and features interesting examples of the consequences of the interdependencies identified.Findings - The paper concludes that the strong emphasis on coordination of sequential interdependence within individual supply chains does not fit with the complex interdependencies present in and among supply chains and projects in construction. In addition to sequential interdependence it describes and illustrates pooled interdependence based on joint resource utilisation, reciprocal interdependence among activities undertaken at the construction site, and interdependence owing to synchronisation of many supply chains in relation to each and every construction project. The combined effects of these interdependencies challenge traditional SCM recommendations, such as moving activities from the site to the factory.Originality value - The main theoretical argument put forward in this paper is that the application of SCM models developed for other industrial contexts such as the automotive industry, are problematic to use in the construction industry. This is because these models emphasise integration of activities that are subject mainly to sequential interdependencies while the pattern of interdependence is very different in construction. A main implication for practice is that focusing on better planning in order to deal with activities that are mainly subject to sequential interdependence, is insufficient. The reciprocal interdependencies in construction require more frequent and direct interaction among the involved actors to enable mutual adjustments among the firms whose activities and resource use need to be coordinated.